Abnormal Glycosylation of Cancer Stem Cells and Targeting Strategies - Khan, Thahomina; Cabral, Horacio (Frontiers in Oncology, 2021)
Cancer stem cell (CSCs) are deemed as one of the main reasons of tumor relapse due to their resistance to standard therapies. Numerous intracellular signaling pathways along with extracellular features are crucial in regulating CSCs properties, such as heterogeneity, plasticity and differentiation. Aberrant glycosylation of these cellular signaling pathways and markers of CSCs have been directly correlated with maintaining survival, self-renewal and extravasation properties. In this review, we highlight the importance of glycosylation in promoting stemness character of CSCs, and present strategies for targeting abnormal glycosylation to eliminate the resistant CSC population.